Concepts and Methods of 2D Infrared Spectroscopy / [electronic resource] - Hamm, Peter; Zanni, Martin (Cambridge : Cambridge University Press, 2011)
2D infrared (IR) spectroscopy is a cutting-edge technique, with applications in subjects as diverse as the energy sciences, biophysics and physical chemistry. This book introduces the essential concepts of 2D IR spectroscopy step-by-step to build an intuitive and in-depth understanding of the method. This unique book introduces the mathematical formalism in a simple manner, examines the design considerations for implementing the methods in the laboratory, and contains working computer code to simulate 2D IR spectra and exercises to illustrate involved concepts. Readers will learn how to accurately interpret 2D IR spectra, design their own spectrometer and invent their own pulse sequences. It is an excellent starting point for graduate students and researchers new to this exciting field. Computer codes and answers to the exercises can be downloaded from the authors' website, available at www.cambridge.org/9781107000056.
Title from publisher's bibliographic system (viewed on 09 Oct 2015).
Keywords: Infrared spectra